2009
DOI: 10.1016/s1567-5688(09)70115-1
|View full text |Cite
|
Sign up to set email alerts
|

Abstract: P746 PREPROCEDURAL C-REACTIVE PROTEIN PREDICTIVE VALUE IN ANGIOGRAPHIC IN-STENT RESTENOSIS AFTER CORONARY STENT PLACEMENT IN PATIENTS WITH STABLE ANGINA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Since interventional cardiologists are being asked to perform PCI on increasing numbers of elderly patients with significant co-morbidities, such as diabetes and/or renal insufficiency, contrast nephropathy is a potentially serious complication of PCI [ 24 , 25 ]. Other risk factors also should be taken into accounts as contributors of PCI complications and adverse outcomes [ 26 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since interventional cardiologists are being asked to perform PCI on increasing numbers of elderly patients with significant co-morbidities, such as diabetes and/or renal insufficiency, contrast nephropathy is a potentially serious complication of PCI [ 24 , 25 ]. Other risk factors also should be taken into accounts as contributors of PCI complications and adverse outcomes [ 26 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are considered risk factors for serious diseases such as heart diseases and cancers (35)(36)(37)(38). Various studies reviewed in this study showed that Ber attenuated DOX-induced nephrotoxicity by reducing total reactive oxygen species (ROS), lipid peroxides, NF-κB p65, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and caspase-3 (39).…”
Section: Discussionmentioning
confidence: 98%
“…Over the last years, several studies have suggested that some factors, e.g. endothelin-1, C-reactive protein (CRP), dimethylarginine, haptoglobin polymorphism, transforming growth factor β (TGF-β), heat shock protein 70 (HSP70), plasma nitric oxide (NO) and vascular endothelial growth factor (VEGF), could be markers of risk for endothelial dysfunction and have an impact on long-term prognosis in patients with CAD [45][46][47][48][49][50][51][52][53][54][55]. Some studies showed that proton pump inhibitor based therapy may have beneficial effects in patients with CAD.…”
Section: Hypertension Update 2011mentioning
confidence: 99%